Use of Deep Plane facelift technique for Resection of Facial Plexiform Neurofibromatosis: A Case Report - Qanah, Sadeq; Salih, Safwan (Brazilian Journal of Case Reports, 2025)
Facial plexiform neurofibromatosis presents a significant treatment challenge due to its infiltrative behavior and location in aesthetically sensitive region. These tumors lack clear boundaries, requiring meticulous surgical planning to balance tumor control and cosmetic outcomes. We report a 36-year-old male with a long-standing painless swelling on the left periorbital and temporal region.clinical findings and family history were consistent with neurofibromatosis type 1. A deep plane facelift approach was used for tumor debulking. histopathological confirmation was obtained. The patient had an uneventful recovery with excellent aesthetic results over a 15-month follow-up. The deep plane facelift technique offers a novel and effective approach for managing facial plexiform neurofibromatosis, preserving facial symmetry and minimizing scarring.